2018
DOI: 10.1051/0004-6361/201833649
|View full text |Cite
|
Sign up to set email alerts
|

Warped disks during type II outbursts in Be/X-ray binaries: evidence from optical polarimetry

Abstract: Context. Current models that explain giant (type II) X-ray outbursts in Be/X-ray binaries (BeXB), are based on the idea of highly distorted disks. They are believed to occur when a misaligned and warped disk becomes eccentric, allowing the neutron star to capture a large amount of material. The BeXB 4U 0115+63 underwent two major outbursts in 2015 and 2017. Aims. Our aim is to investigate whether the structural changes in the disk expected during type II outbursts can be detected through optical polarimetry. M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The Type II outbursts are more luminous (typical luminosity > 10 37 ergs s −1 ), less common and these outbursts are probably caused by episodes of sudden mass eruption from the Be star or due to accretion from the warped disc ⋆ E-mail: amar.deo.chandra@gmail.com of the Be star which does not lie in the orbital plane of the binary system. However the exact mechanism of the eruptions is still poorly understood (Reig 2011;Cheng et al 2014;Reig & Blinov 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Type II outbursts are more luminous (typical luminosity > 10 37 ergs s −1 ), less common and these outbursts are probably caused by episodes of sudden mass eruption from the Be star or due to accretion from the warped disc ⋆ E-mail: amar.deo.chandra@gmail.com of the Be star which does not lie in the orbital plane of the binary system. However the exact mechanism of the eruptions is still poorly understood (Reig 2011;Cheng et al 2014;Reig & Blinov 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Spectropolarimetric observations of Be stars over decades have shown variation in V-band polarization as the Be disk dissipates and a new disk shows up [40]. Polarimetric observation of the Be/X-ray binary 4U 0115+63, covering a giant outburst, has shown that the polarization degree and angle changed significantly while the Be disk warped [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to its very well constrained orbital parameters, many models for Be/X-ray binaries are based on this source . Giant outbursts in this system have been associated with the presence of a tilted disk around the Be star (Reig et al 2007;Martin et al 2011;Kato 2014) and the timescale between subsequent giant outbursts has been estimated to be 3 yrs, even though sometimes these outbursts can occur 1-1.5 yrs apart (Reig et al 2007;Reig & Blinov 2018). Note that, for this system, the ZLK oscillations of the Be star disk might operate on a timescale that matches the observed 3 yr frequency of type II outbursts, provided that the disk is not completely destroyed during the outburst .…”
Section: Misaligned Be Star Disk Simulationmentioning
confidence: 93%
“…In general, type II outbursts last several binary orbital periods (Kretschmar et al 2012). Reig & Blinov (2018) found that type II outbursts often occur in pairs with the second one being less luminous than the first. Type II outbursts may be explained by the presence of a highly misaligned Be star disk that becomes eccentric due to the Von Zeipel-Lidov-Kozai (ZLK) mechanism (von Zeipel 1910;Kozai 1962;Lidov 1962) and transfers mass through Roche lobe overflow onto the neutron star (Martin et al 2014b,a;Fu et al 2015a;.…”
Section: Introductionmentioning
confidence: 99%